An analysis of sexist language between women and men on social media pages - Anima Putri Fadillah; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This article aims to analyze the language of women and men. One of the things that affect language is gender. The theory used in this study is This study uses theory from Coates (2004) about male language features and Lakoff cited by Holmes (2003) about female language. The language differences between women and men here are regarding language features, their vocabulary, and topics that are usually discussed. This study uses a qualitative method. The data source is taken from social media conversations in the form of Whats App. The collected data will be analyzed using descriptive techniques to draw conclusions. The results of this study will then reveal some differences in conversations between women and men.